Cross‐Country Heterogeneity in Students' Reporting Behavior: The Use of the Anchoring Vignette Method. Issue 1 (1st March 2018) - Vonkova, Hana; Zamarro, Gema; Hitt, Collin
Abstract: Self‐reports are an indispensable source of information in education research but they are often affected by heterogeneity in reporting behavior. Failing to correct for this heterogeneity can lead to invalid comparisons across groups. The researchers use the parametric anchoring vignette method to correct for cross‐country incomparability of students' reports on teacher's classroom management. Their analysis is based on the data from the Programme for International Student Assessment 2012. The results show significant variation in implicit standards across countries. Correlations between countries' average teacher classroom management levels and external variables like students test scores and public expenditure per pupil change substantially after vignette adjustment. The researchers conclude that the anchoring vignettes method shows potential to enhance the comparability of self‐reported measures in education.